Forest fire size amplifies postfire land surface warming - Zhao, Jie; Yue, Chao; Wang, Jiaming; Hantson, Stijn; Wang, Xianli; He, Binbin; Li, Guangyao; Wang, Liang; Zhao, Hongfei; Luyssaert, Sebastiaan (Nature (London), 2024)
Climate warming has caused a widespread increase in extreme fire weather, making forest fires longer-lived and larger 1 – 3 . The average forest fire size in Canada, the USA and Australia has doubled or even tripled in recent decades 4 , 5 . In return, forest fires feed back to climate by modulating land–atmospheric carbon, nitrogen, aerosol, energy and water fluxes 6 – 8 . However, the surface climate impacts of increasingly large fires and their implications for land management remain to be established. Here we use satellite observations to show that in temperate and boreal forests in the Northern Hemisphere, fire size persistently amplified decade-long postfire land surface warming in summer per unit burnt area. Both warming and its amplification with fire size were found to diminish with an increasing abundance of broadleaf trees, consistent with their lower fire vulnerability compared with coniferous species 9 , 10 . Fire-size-enhanced warming may affect the success and composition of postfire stand regeneration 11 , 12 as well as permafrost degradation 13 , presenting previously overlooked, additional feedback effects to future climate and fire dynamics. Given the projected increase in fire size in northern forests 14 , 15 , climate-smart forestry should aim to mitigate the climate risks of large fires, possibly by increasing the share of broadleaf trees, where appropriate, and avoiding active pyrophytes. Climate warming has increased forest fire sizes, amplifying postfire summer warming, with broadleaf trees mitigating this effect; climate-smart forestry should increase broadleaf tree cover to manage future fire risks.